Piezofluorochromism in Charge‐Transfer Inclusion Crystals: The Influence of High Pressure versus Mechanical Grinding. Issue 5 (5th March 2018) - Ono, Toshikazu; Tsukiyama, Yoshifumi; Taema, Ai; Sato, Hiroyasu; Kiyooka, Hidetoshi; Yamaguchi, Yuma; Nagahashi, Ayumi; Nishiyama, Manami; Akahama, Yuichi; Ozawa, Yoshiki; Abe, Masaaki; Hisaeda, Yoshio
Abstract: The distinct piezochromic luminescent responses of charge−transfer inclusion crystals, which consist of small aromatic guest molecules with naphthalenediimide derivatives, are reported. Reversible multichromism is observed over the entire visible region in response to high pressure, whereas a weak response to mechanical grinding is evident. High‐pressure single‐crystal X‐ray diffraction analysis and TD‐DFT calculations clearly suggest that high compression induces a closer arrangement with a short interfacial distance between small aromatic guest molecules and naphthalenediimide derivatives, which is proposed as the origin of the drastic luminescent color change. Abstract : A close call : A series of charge‐transfer complexes showed reversible multichromism over the entire visible region in response to high pressure but demonstrated only a weak response to mechanical grinding. High‐pressure X‐ray diffraction analysis and TD‐DFT calculations suggest that high compression induces a short interfacial distance between the donor and acceptor in charge−transfer complexes, which is the origin of the drastic luminescent color change.